دور ﺣزب اﻟﻌداﻟﺔ واﻟﺗﻧﻣﯾﺔ اﻟﺗرﻛﻲ ﻓﻲ اﻟﺻراع اﻻﯾدﯾﻠوﺟﻲ ﻷﻧﺿﻣﺎم ﺗرﻛﯾﺎ اﻟﻰ اﻻﺗﺣﺎد اﻻورﺑﻲ (Journal of the College of Education for Women, 2019)
Talking about Turkey joining the European Union does not mean a few conditions implemented by Turkey Vtostagib Europe torequest or do not respond, it is a further and much deeper than that, The issue is of historic proportions, cultural, and political develop a European identity itself to the test, and determine the future of the continent and the entire region for generations to come, and has repercussions economic, social and cultural scene to lend further complexity, some of what is important and beneficial to both parties, some of which deepens the fears of both. Here we can point out the fear of invasion of Islam to Europe, which is a real fear belong to the type of phobia disease produced by the categories of right-wing Christian and Jewish Zionism in Europe, where you see these categories that even if Turkey entered all the criteria to join the European Union particularly with regard to human rights , and achieved a political and economic reforms essential, but it should not be allowed to enter the Union, because the entry, "they said," would be a threat to the identity and civilization of Christian Europe, and it seems that these are currently the most powerful stakeholders in the industry, the European decision, but they cannot declare their refusal to Turkey to join, either directly or through public officials, because that would lead to serious negative repercussions. Therefore, the European Union seek to bypass roads to reject Turkey's membership, including what has become known as Plan "B" and requires the plan to grant Turkey (special position) and this situation, which is less than full membership, which would give Turkey a number of features of special economic relations with the European Union, However, some, including European countries and the Netherlands, insist that there is no such thing as a plan "B", either to become a full member of Turkey, or remain at the gates of the European Union forever. Many observers believe that the main obstacle to Turkey's entry into the Union is in the religious side, that is because of the identity of Muslim Turkey, especially if we know that most of the new states in the Union failed to implement fully the requirements, but Europe cannot speak as to this matter, because it would lose its credibility , undermines all her claims of freedom and democracy that make up the main title in the European identity and civilization, but that this Satabaha nature of racism, but this turned to Europe Drags style, you will not stop fabricated claims and put barriers up to change the face of the European continent.